Analysis of the Shifting Process of the Mercedes Benz 722.9 Automatic Transmission based on the Expansion of the Lever Method - Hou Guoqiang; Li Jinghua; Li Haibin; Cheng Qiqiang (Jixie chuandong)
In the light of the defect and deficiency of the lever method in the analysis of the transmission of multi planetary gear transmission,it is expanded and improved.By using the new extended lever method,the transmission of each shift of the Mercedes Benz 722.9 Automatic transmission is analyzed.And the correctness of the extended lever method and the analysis are verified.